Peran Guru Pendidikan Agama Islam dalam Menginternalisasi Nilai-nilai Kesetaraan Gender di SMP BP Daarussholah - Muhammad Yoga Julyanur; Mahfud Ifendi; Tri Velyna (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine the values of gender equality in Daarussholah Pesantren-Based Junior High School (BP), the role of Islamic Religious Education (PAI) teachers in internalizing it, as well as the supporting and inhibiting factors in the process. This research uses a qualitative approach with a field method. Data were collected through observation, interviews, and documentation with the main informants, namely PAI teachers, students, and principals. Data analysis used the Miles and Huberman model which includes data collection, data reduction, data presentation, and conclusion drawing.The results showed that Daarussholah Pesantren-Based Junior High School has attempted to implement gender equality values through policies that support equal rights and opportunities between male and female students, both in learning, leadership, and extracurricular activities. These values include justice, equality, and freedom of expression without gender restrictions. PAI teachers play an important role as educators and role models, conveying these values through teaching, social interaction and support for the school's inclusive policies. Supporting factors for the internalization of these values are the progressive school policies and the diversity of the teaching staff. Meanwhile, the inhibiting factor is the immaturity of students' emotional intelligence.